Drivers of vulnerability to health and wellbeing challenges in informal settlements - Chumo, Ivy; Kabaria, Caroline; Shankland, Alex; Mberu, Blessing (Frontiers in Sustainable Cities, 2023)
Introduction It is widely acknowledged that vulnerable populations are hit very hard, both in the short and long term, when their health and wellbeing needs are not met. Despite the efforts at different levels to protect and promote their health and wellbeing, older persons, people with disabilities and children heads of households, continue to face significant social, economic and cultural difficulties in relation to health and wellbeing inequities. While rights to health and wellbeing are constitutionally guaranteed, and strategies can be advanced to reduce vulnerable situations, challenges persists and yet societies, communities, and individual factors that engender vulnerability are understudied and remain poorly understood. Situating our findings and understandings within CLUVA social vulnerability framework, allows us to adapt a conceptual framework for understanding vulnerability to health and wellbeing challenges across different groups in informal urban space. We used CLUVA social vulnerability framework to explore and uncover drivers of vulnerability to health and wellbeing challenges among the vulnerable and marginalized groups using the governance diaries approach. Methods This was an ethnographic study, using governance diaries with 24 participants in Korogocho and Viwandani informal settlements in Nairobi, Kenya. The governance diaries approach involved bi-weekly governance in-depth interviews (IDIs) with study participants for 4 months, complemented with observations, reflections, participant diaries and informal discussions. We used framework analysis methodology. Results We identified several interlinked drivers and grouped them as individual, community, societal and structural level factors. Discussion A comprehensive view of drivers at different levels will help actors engage in more expansive and collaborative thinking about strategies that can effectively reduce health and wellbeing challenges. Conclusion The factors identified come together to shape functioning and capabilities of vulnerable groups in informal settlements. Beyond applying a more comprehensive concept of understanding health and wellbeing challenges, It is important to understand the drivers of vulnerability to health and wellbeing challenges from the perspective of marginalized and vulnerable populations. Particularly for local urban planning, the information should blend routine data with participatory assessment within different areas and groups in the city.